Effects of fruit and vegetable consumption on inflammatory biomarkers and immune cell populations: a systematic literature review and meta-analysis. Issue 1 (21st June 2018) - Hosseini, Banafshe; Berthon, Bronwyn S; Saedisomeolia, Ahmad; Starkey, Malcolm R; Collison, Adam; Wark, Peter A B; Wood, Lisa G
Abstract: BACKGROUND: Inflammation is associated with an increased risk of a range of chronic diseases. A diet high in fruit and vegetables may help to reduce inflammation, as fruit and vegetables are rich sources of antioxidants and other biologically active substances, which may improve immune function. OBJECTIVE: To summarize the evidence, we executed a systematic review and meta-analysis examining the effects of fruit and/or vegetable intake on inflammatory biomarkers and immune cells in humans with different diseases and conditions. Design: Electronic databases including PubMed, Cochrane, CINAHL, and EMBASE were systematically searched up to March 2018. RESULTS: Eighty-three studies were included. Of these, 71 (86%) were clinical trials, and 12 were observational studies ( n = 10 cross-sectional and n = 2 cohort). Amongst the observational research, n = 10 studies found an inverse association between intakes of fruit or vegetables and inflammatory biomarkers. Similarly, the majority of the intervention studies (68%, n = 48) reported beneficial effects of fruit or vegetable intake on ≥1 biomarker of systemic or airway inflammation. A meta-analysis of included studies showed that fruit or vegetable intake decreased circulating levels of C-reactive protein and tumor necrosis factor-α ( P < 0.05) and increased the γδ-T cell population ( P < 0.05). Conclusions: In conclusion, this review suggests that higher intakes of fruit and vegetables lead to both a reduction in proinflammatory mediators and an enhanced immune cell profile.